SNP-based linkage mapping reveals novel quantitative trait loci for yield traits in noug (Guizotia abyssinica (L. f.) Cass.) - Gebeyehu, Adane; Hammenhag, Cecilia; Vetukuri, Ramesh R.; Ortiz, Rodomiro; Geleta, Mulatu (Frontiers in Plant Science, 2025)
Noug (Guizotia abyssinica) is a vital Ethiopian oilseed crop lacking comprehensive genomic resources. This study constructed the first high-density SNP-based linkage map for this diploid species (2n=30, genome size ~1.7 Gb). Using an F2 mapping population of 286 individuals, we generated 13,888 high-quality SNPs from genotyping-by-sequencing (GBS), which were mapped onto 15 linkage groups (LGs) with a mean marker density of 2.1 cM, covering 90.6% of the genome. Phenotypic evaluation revealed significant variation for nine agronomic traits, including plant height (110–292 cm), days to flowering (49–115 days), and oil content (13.88–55.62%). Quantitative trait loci (QTL) mapping identified 27 QTL for six traits. Major findings include a flowering time QTL (qDTF-9-1) on LG9 explaining 7.6% of phenotypic variation (PVE) and a seed yield QTL (qNSPP-5-1) on LG5 explaining 2.9% PVE. Comparative genomics with sunflower (Helianthus annuus) revealed significant synteny, enabling the identification of candidate genes underlying these QTL: CLC-b (for qDTF-9-1) and GPT1 (for qNSPP-5-1). Additional QTL were detected for thousand-seed weight (cumulative PVE 51.2%), flower size (47.5%), capitula number (32.8%), and oil content (38.1%). This high-density genetic map and the identified QTL provide a foundational genomic resource for marker-assisted breeding to improve yield and agronomic traits in noug.